A New Glass Bead Game: Redesigning the Academy - Nelson, Don (Paideusis, 2008)
The academy has gained a reputation as a place of authoritative statements, truth, and insight as a result of its long history. Yet during that history its authority to make definitive statements has been built on different foundations—now overlapped and layered. Each source of authority has buried, overlaid, or sometimes supplanted the previous one while the institution has carried on. Is this historical value still solid or is it threatened by the conditions we find ourselves in today? As members of the academy, perhaps we need to ask ourselves about the foundations on which we build and the functions that the Academy may yet serve in society. Using thoughts inspired by Herman Hess’s Magister Ludi, this paper explores those questions.